2017
DOI: 10.18697/ajfand.79.16005
|View full text |Cite
|
Sign up to set email alerts
|

Factors that negatively influence consumption of traditionally fermented milk (mursik) among preschool children (1-5 years old) in Kapseret location -Uasin Gishu County, Kenya

Abstract: Traditionally fermented milks are widely consumed in various countries of sub-Saharan Africa and a number of health benefits to human beings are attributed to them. However, available studies show that children less than 5 years old consume milk mainly as fresh milk or when added to tea or porridge. Therefore, information on consumption of traditionally fermented milk by children is scanty, yet factors hindering its consumption have rarely been studied. The objective of this study was, therefore, to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another study found that almost all the caregivers (99 %) used fermented products (milk, yogurt and fermented maize porridge) to nourish children under 5 (21) . According to the research carried out by Kirui et al in Kenya, the use of mursik, which is a probiotic product, was low for children under 5, and families did not have enough information about mursik (27) . The findings of the current study show that the dietary habits of the mothers were very traditional and that they did not have enough knowledge about the benefits of probiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that almost all the caregivers (99 %) used fermented products (milk, yogurt and fermented maize porridge) to nourish children under 5 (21) . According to the research carried out by Kirui et al in Kenya, the use of mursik, which is a probiotic product, was low for children under 5, and families did not have enough information about mursik (27) . The findings of the current study show that the dietary habits of the mothers were very traditional and that they did not have enough knowledge about the benefits of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies in the world investigating the use of probiotics by mothers for their infants and during pregnancy (1,19,21,27) . The knowledge mothers have about probiotics, their attitudes towards them and how they use them during pregnancy and for their infants has not previously been studied in Turkey.…”
mentioning
confidence: 99%
“…According to a survey of 383 Kalenjin families in 2013, 32% of households fed their children (<5 years) with mursik with a mean quantity of 250 mL per week. 32 There is an incentive to let the children consume more mursik due to nutritional needs and a lack of other dairy products. It is well known that acetaldehyde induces nasal and respiratory tract squamous cell carcinoma in rats and hamsters when inhaled.…”
Section: Mursik Consumptionmentioning
confidence: 99%
“…Regular consumption of mursik by young children may contribute to young ESCC in Kalenjins. According to a survey of 383 Kalenjin families in 2013, 32% of households fed their children (<5 years) with mursik with a mean quantity of 250 mL per week 32 . There is an incentive to let the children consume more mursik due to nutritional needs and a lack of other dairy products.…”
Section: Studies On Ec In Kenyamentioning
confidence: 99%
“…Low calcium consumption might have been due to milk commercialization by most of the households in Uasin-Gishu instead of feeding it to the children. Kirui and Nguka [23] in a survey on the influence of milk consumption among children 1 -5 years in Uasin-Gishu County established that a smaller percentage of the households (32%) fed their children with a mean quantity of 250 ml of milk per week. Tanaka et al, [24] established that daily milk consumption was significantly associated with a lower risk of dental caries in children.…”
Section: F Calcium and Phosphorusmentioning
confidence: 99%